RESULTS OF EARLY PHYSICAL REHABILITATION IN PATIENTS AFTER CORONARY ARTERY BYPASS SURGERY - V. V. Bazylev; N. V. Galtseva (Klinicist)
The study objective is to examine the effectiveness of physical rehabilitation in patients after coronary bypass surgery at the stationary stage.Materials and methods. The study included 112 patients with ischemic heart disease and saved systolic function of the left ventricle (heart ejection fraction >35%) after coronary artery bypass surgery (CABS). The first group consisted of 60 patients who received standard program of physical rehabilitation with controlled training on treadmill in early postoperative period. Cardiovascular exercises with intensity of 3–6 metabolic equivalents (MET) started at 3–4 days after surgery on treadmill and continued until discharge from the hospital; simultaneously careful monitoring  of hemodynamic parameters was performed. The second (control) group included 52 patients who received standard physical rehabilitation activities. At the end of stationary stage of physical rehabilitation all patients completed the questionnaire SF-36 Health Status Survey.Results. Initially, according to clinical, demographic and perioperative characteristics the compared groups did not differ statistically. At the end of the program of physical rehabilitation for the average value of the total post-operative bed-day in the first (median was 8) and in the second group (median was 9) statistically significant differences were obtained (p <0.0001), which were in favor of the studied population. In the first group tolerance to physical exertion increased by 3 MET and in general it was 6 MET. According to the results of the questionnaire SF-36 in the group of patients with cardiovascular exercises, the average indexes of physical, role functioning, mental health were significantly different from the results in the control group (accordingly p = 0.0038, p <0.0001, p = 0.033).Conclusion. Implementation in the program of physical rehabilitation in patients after CABG controlled cardiovascular exercise on treadmill at a hospital stage does not increase the incidence of complications, and the use of elements of early rehabilitation help to improve tolerance to physical exertion. In addition, the program of early physical rehabilitation improves subjective health parameters according to the questionnaire of life quality assessment SF-36 and reduces the duration of the postoperative bed-day.